EFL Students' Perceptions toward the Integration of Bahasa Indonesia (L1) In English Language Teaching - Nizar Saputra; Asirah Asirah (Universitas Pendidikan Mandalika, Faculty of Culture, Management, and Business (UNDIKMA), 2022)
The application of the first language (L1) in English language teaching (ELT) has long been practiced, and its practice has been controversial in foreign language teaching. This research aims to investigate students' attitudes toward the application of Bahasa Indonesia (Indonesian students' L1) in ELT. This research is framed through a quantitative survey in which the 32 participants were invited to take online self-administered questionnaires. Result suggests that the integration of Bahasa Indonesia in English language teaching as a pedagogical tool is considered beneficial to improve students' English proficiency, enhance English vocabulary, and improve comprehension. In addition, the participants also believed that the numerous use of L1 or Bahasa Indonesia may provide less opportunity for students to develop their speaking skills. When it comes to preferences of language use in ELT, most students agreed that their English teachers should integrate both Bahasa Indonesia and English, in which the use of Bahasa Indonesia to be minimized while English to be predominated.